A organização da educação no território federal do Amapá: do "ideal" ao real, do liberal ao conservador (1943-1958) - Dias, Ana Olga da Silva (2014)
The present study on “organization education on Amapá’s Federal Territory (1943-1958)”, looked forward to answering the following questions: Was there an educational policy, in a systemic way, on the former Amapá’s federal territory? On the other hand, what were the main initiatives of the first intervenors for the education dissemination? After facing these questions, we established, as hypothesis, that the developed actions in the education’s scope on that territory back in the 40’s and 50’s were not able to implant an educational project in Amapá, since there was no preoccupation to understanding the sociocultural reality of Amapá’s population. Given this hypothesis, we analyzed the relation between the political practices developed by the first intervenor on the territory and the brazilian political scenario, from the legal-administrative nature of the federal entities and political conjuncture of the “New State” (1937-1945). To achieve that, we sought some similarities between Janary Gentil Nunes’s ways of governing and Getúlio Vargas’s political actions. To make this happen, it was necessary to check official documents out, as well as unofficial ones, especially the old articles published by “Amapá”, the local newspaper, official press tool back then, which disseminated the beliefs and values of the constituted authorities, with the purpose of “strengthen” the “modernization” ideal on the people. Such practice was based on the attempt of breaking off sociocultural economic backwardness of the territory, hiding out the reality of the Amapá’s population, marked by poverty, a high illiteracy rate and the typical tropical diseases from Amazon (Malaria). During the rupture’s process between the old and the modern, the education takes on a major role in the official speech, being used as political advertisement and as essential element to the modernization and to the development of a “new man”: now “civilized”. However, the investigation on the expansion of the elementary education in Amapá, showed us the presence of a significant number of rural schools, in contradiction to the disseminated urban modernization promise around there. In this sense, we can affirm that educational policy on Amapá’s territory failed by reasons of being based on the “transplantation” of the Federal District’s educational project, and it is important to recall that, back then, the brazilian Federal District was Rio de Janeiro. Despite the public agents had established uncountable schools on rural areas, these were not carried out from a more systemic process, this is, considering the reality of the Amazon’s "cabloco". So, we observed the existence of the separation between the modern speech and the maintenance of old oligarchic practices by that time.